2021
DOI: 10.3390/ijms22158291
|View full text |Cite
|
Sign up to set email alerts
|

On the Consistency of the Exfoliation Free Energy of Graphenes by Molecular Simulations

Abstract: Monolayer graphene is now produced at significant yields, by liquid phase exfoliation of graphites in solvents. This has increased the interest in molecular simulation studies to give new insights in the field. We use decoupling simulations to compute the exfoliation free energy of graphenes in a liquid environment. Starting from a bilayer graphene configuration, we decouple the Van der Waals interactions of a graphene monolayer in the presence of saline water. Then, we introduce the monolayer back into water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The nanosheets are amenable to precise surface modifications, while their exquisitely thin profiles enable their deposition or integration into different substrates or matrices [9,10] . Graphene holds an intriquing appeal for fundamental research through molecular simulation studies, allowing materials design and modeling at the molecular level [11–13] . In alignment with the evolving state‐of‐the‐art concepts of molecular engineering and architecture, [14] graphene, as a raw material, provides a foundation for harnessing and exploiting chemistry in increasingly innovative ways.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nanosheets are amenable to precise surface modifications, while their exquisitely thin profiles enable their deposition or integration into different substrates or matrices [9,10] . Graphene holds an intriquing appeal for fundamental research through molecular simulation studies, allowing materials design and modeling at the molecular level [11–13] . In alignment with the evolving state‐of‐the‐art concepts of molecular engineering and architecture, [14] graphene, as a raw material, provides a foundation for harnessing and exploiting chemistry in increasingly innovative ways.…”
Section: Introductionmentioning
confidence: 99%
“…These methods create force fields akin to shear forces, which, although not precisely quantified, provide the necessary energy to temporarily separate strongly adhered layers of 2D materials. In this context, molecular dynamics simulations have convinsingly verified that the favored reaction coordinate for the delamination of layered materials is on the shear direction [32] . In particular, steered molecular dynamics (MD) have shown that it requires essentially less force to pull the exfoliating graphene sheet parallel (shear) to the basal plane of the graphite than perpendicular to it [12,33,34] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is with this motivation that we simulate the free energy of different carbon frameworks crossing hydrophobic-hydrophilic solvents [18,19]. Practicing with well-defined force fields (all-carbon solids, cyclohexane as the organic solvent, and SPC water) helps the formulation and execution of a sustainable workflow commited to free energy simulations [20][21][22][23][24][25]. The workflow is a precursor on an ongoing computational campaign investigating the binding affinities of such materials embedded in conjugated solvents with larger molecules such as polymers, surfactants, or lipids [26,27].…”
Section: Introductionmentioning
confidence: 99%